Urgent Care for Educators : Situating Responsibility as a Way for Educators to Transform School Cultures - Smith, Barbara J., (Educational Research E-Books Online, Collection 2026., 2025)
Urgent Care for Educators is a resource that responds to the question: How can students be expected and encouraged to be responsible in schools, if education systems do not provide a culture of responsibility for the adults in the building? This collection written by teachers and teacher leaders in responsible roles features case stories from new and experienced educators who share their stories as service providers, injustice responders, action researchers, social designers, teachers of teachers and apprentices. This read provides ample evidence that it can be done! Contributors are: June Abbott, Philip Alcock, Mike Babb, Kevin Bartlett, Briza Bohne , Evan Coleman, Luke Coles, Nick Davies, Jackie Delong, Andrea Fanjoy, Kate Anderson Foley, David Franklin, Lisa Gonzales, Stuart Grauer, Michelle Hughes, Michele Jones, Tanya Knudsen, Martha J. Koch, Michael Lawrence, Liz Locatelli, Jose Antonio Gordillo Martorell, Janine Meadley, Matthew Panayotopoulos, Angela Purcell, Douglas Reeves, Jessika Shields, Barbara J. Smith, Larry Swartz, Tracey Tinley, Tanya Upthegrove Gregory, Adam Watson, Gennifer Williams, and Rick Wormeli.